Effect of Visit Frequency of Pharmacist-Led Diabetes Medication Management Program. (February 2022) - Frederick, Amy; Juan, Joyce; Ivy, Delaney; Maldonado, Yolanda Munoz
Background: Pharmacists have a positive effect on clinical outcomes in chronic disease state management, however, few studies have evaluated the effect that frequency of visits may have on diabetes biomarkers such as hemoglobin A1c and blood pressure readings. Methods: Under the medication management program (MMP), patients with diabetes were seen monthly by pharmacists until early 2015, when time between visits was increased to every 3 months. A retrospective chart review was conducted to evaluate the primary outcome of the percent change in hemoglobin A1c and blood pressure after the change in visit frequency. Results: In the 303 patients enrolled, no statistical difference existed between the pre and post average A1c (p-value = 0.10). The intermediate average A1c was statistically lower from the preintervention mean A1c (p-value = 0.001) but not from the postintervention mean A1c (p-value = 0.30). No statistical differences were seen between systolic blood pressure and diastolic blood pressure. Conclusion: Patients who have been seen by a clinical pharmacist more frequently (every month or every other month) for several years may be able to maintain their reduction in A1c with less-frequent visits (every 3 to 6 months).